Internalization strategies and value implications of latin american emerging market multinationals - Ficici, Aysun; Aybar, C. Bulent (Internext, 2009)
This study investigates the Internationalization strategies and their value implications of Latin American Emerging Market Multinationals (LAEMMs). We examine 66 mergers and acquisitions (M&A) announcements, 20 joint venture (JV) announcements and 9 Strategic Alliance (SA) announcements associated with LAEMMs during the sample period of 1991-2005. First, the paper explores the effects of cross-border expansion patterns on firm value creation. Second, it examines market reaction to the announcements of cross-border expansion patterns. Third, it evaluates firm performance in relation to the cross-border expansion activities. This study finds that most LAEMMs do not earn significantly positive abnormal returns during the event windows defined in this study. However, it is generally evident that there is value creation in international expansion activities. According to the event-study results, value creation is mostly associated with SAs. This finding is consistent with previous research. It is also indicated that most SA announcements are received by the market positively. JVs also experience value creation during the event windows utilized in this study. However, value creation of JVs is not to the extent that of SAs. Market reaction to JV announcements is also positive, but not to the degree of SAs.